The System of Preparing Future Teachers for Professional Innovative Activities - Hakim qizi, Naimova Zarnigor (European Journal of Life Safety and Stability (2660-9630), 2022)
This article presents the actual state of the system of professional preparation of future pedagogues for innovation activity in the sphere of education. Based on the results of two interrelated examinations – individual expert assessments and subsequent expert discussions in special groups – the author defines the key issues in the streamlining of the system under study and puts forward specific suggestions on resolving them.